2021
DOI: 10.3389/fgeed.2021.722190
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of 12-Hydroxyeicosatetraenoic Acid, Single Nucleotide Polymorphisms of 12-Lipooxygenase Gene and Vaso-Occlusion in Sickle Cell Disease

Abstract: Background and Novel Aspect of this Work: In the light of previous findings that inflammation predisposes to intercellular adhesion and microvascular occlusion in sickle cell disease (SCD), this study investigated the relationship between the number of vaso-occlusive events in SCD, plasma levels of the pro-inflammatory molecules 12-Hydroxyeicosatetraenoic acid (12-HETE), TNF-α and IL-1β; and single nucleotide polymorphisms (SNPs) in the gene 12-Lipooxygenase (ALOX-12), which encodes the enzyme 12-Lipoxygenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Mazi et al [83] recently showed that plasma levels of LOX products derived from ARA were higher and certain CYP product metabolites were lower in Caucasians compared to White Hispanics with nonalcoholic steatohepatitis. On the other hand, few differences in oxylipins due to race/ethnicity were found in healthy children at risk for type 1 diabetes [38], and no differences in 12-HETE levels were associated with 12-LOX polymorphisms in the context of vasoocclusion in sickle cell disease [84]. Environment can also interact with genotype, as HEPE and HDoHE oxylipins increase more in response to EPAþDHA supplementation in those with the apolipoprotein E4 compared to the E3/E3 genotype [85].…”
Section: Biological Variation Of Oxylipins -Sex Genetics and Environmentmentioning
confidence: 99%
“…Mazi et al [83] recently showed that plasma levels of LOX products derived from ARA were higher and certain CYP product metabolites were lower in Caucasians compared to White Hispanics with nonalcoholic steatohepatitis. On the other hand, few differences in oxylipins due to race/ethnicity were found in healthy children at risk for type 1 diabetes [38], and no differences in 12-HETE levels were associated with 12-LOX polymorphisms in the context of vasoocclusion in sickle cell disease [84]. Environment can also interact with genotype, as HEPE and HDoHE oxylipins increase more in response to EPAþDHA supplementation in those with the apolipoprotein E4 compared to the E3/E3 genotype [85].…”
Section: Biological Variation Of Oxylipins -Sex Genetics and Environmentmentioning
confidence: 99%